Selenomethionine against titanium particle-induced osteolysis by regulating the ROS-dependent NLRP3 inflammasome activation via the β-catenin signaling pathway - Yu, Ruixuan; Yuan, Yongjian; Liu, Zhicheng; Liu, Long; Xu, Zhaoning; Zhao, Yunpeng; Jia, Chunwang; Zhang, Pengfei; Li, Hang; Liu, Yuhao; Wang, Yi; Li, Weiwei; et al. (Frontiers in Immunology, 2023)
Wear debris-induced osteolysis, especially titanium (Ti) particles-induced osteolysis, is the most common cause of arthroplasty failure with no effective therapy. Previous studies have suggested that inflammation and impaired osteogenesis are associated with Ti particles -induced osteolysis. Selenium (Se) is an essential trace element in the human body, which forms selenomethionine (Se-Met) in nature, and selenoproteins has strong anti-inflammatory and antioxidant stress effects. In this study, the effects of Se-Met on Ti particles-induced osteolysis were observed and the potential mechanism was explored. We found that exogenous Se-Met relieved osteolysis induced by Ti particles in two animal models and MC3T3-E1 cells. We found that the addition of Se-Met effectively inhibited Ti particle-induced inflammation by regulating reactive oxygen species-dependent (ROS-dependent) NOD-like receptor protein 3 (NLRP3) inflammasome activation. These therapeutic effects were abrogated in MC3T3-E1 cells that had received a β-catenin antagonist, suggesting that Se-Met alleviates inflammatory osteolysis via the β-catenin signaling pathway. Collectively, these findings indicated that Se-Met may serve as a potential therapeutic agent for treating Ti particle-induced osteolysis.